THE ROLE OF METACOGNITIVE STRATEGIES TRAINING IN TEACHING ENGLISH IN INDONESIAN EFL CLASSROOMS - Mike Nurmalia Sari (Sekolah Tinggi Pariwisata Mataram, 2021)
This article aims to explore the roles of metacognitive strategies training in teaching English, especially as a foreign language as it is learnt in Indonesia. Teacher should teach the students in order to help the students to understand the materials in both form of concepts and methods. In order to teach the students well, the teacher must construct and teach an appropriate learning strategies, choose appropriate media, and develop positive atmosphere of teaching and learning process. Thus, it is important to develop students learning strategies to be independent in their learning. The students must improve themselves in learning. They have to be creative manage their learning to control what they are learn and what they are going to learn. Therefore, it is necessary to find out effective learning strategies to overcome those problems. The solution is by providing the effective strategies for teaching Learning Process that is metacognitive strategy. Based on Oxford (1990), metacognitive strategy is the strategy which can help learner to manage their own learning. O’Malley et al (1995) emphasize that learners without metacognitive approaches have no direction or ability to monitor their progress, accomplishments, and future learning directions. Related to students’ problem, the advantages of this strategy can overcome students’ problems because from the beginning of learning activity the students have been asked to analyze the requirement, then to monitor their learning so they know what they should achieve or their purpose. So, this metacognitive strategy can solve students’ learning EFL problem, especially the high school students in Indonesia.